Revision of the South American genus Xiphiola Bolívar, 1896 (Orthoptera: Acrididae: Ommatolampidinae: Abracrini) - Costa, Maria Kátia Matiotti Da; Ferrari, Augusto; Zefa, Edison; Carvalho, Gervásio Silva (Zootaxa, 2016)
The Neotropical genus Xiphiola Bolívar, 1896 is revised. It includes two valid species: Xiphiola borellii Giglio-Tos, 1900 and Xiphiola cyanoptera (Gerstaecker, 1889). The genus and the species are redescribed and diagnostic characters are provided along with illustrations of each species. A lectotype and paralectoype for X. cyanoptera are here designated. We also include new morphological characters from male and female genitalia, and external characters that have not been employed until now. We present the distribution map based on material examined, as well as a key to species.